Interest rate risk immunization - the impact of credit risk in the quality of immunization case study: immunization with Portuguese bonds and German bonds - Rego, L. (2017)
This paper involves an assessment of the interest rate risk present in Financial Institutions and the methods used for its immunization. The paper consists on two parts. The first part presents a theoretical review of the interest rate risk and how this risk can be immunized. Concepts such as Macaulay (1938) and Fisher & Weil (1971) duration and their limitations in the process of the approximation to the price of a considered bond will be highlighted. In the second part the main indicators of the credit risk on bonds are analyzed. Based on market prices of Portugal’s bonds and Germany’s bonds, the quality of immunization is tested. The interest rate derivatives are then introduced as a method of hedging interest rate risk. At the end, an interview is conducted with the responsible for hedging the interest rate risk in one of the largest private banks in Portugal in order to identify the methods used to capture the interest rate risk and to understand how this risk is immunized. This paper allows us to conclude about the importance of credit risk in an immunization strategy of interest rate risk. We conclude that interest rate hedging based on Fisher & Weil (1971) duration is not possible in a scenario of high volatility of credit risk. Interest rate hedge based on interest rate swap becomes more attractive to the Financial Institutions.